2016
DOI: 10.1128/jvi.02969-15
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein-Specific Antibodies Produced by DNA Vaccination Protect Guinea Pigs from Lethal Argentine and Venezuelan Hemorrhagic Fever

Abstract: Several members of the Arenaviridae can cause acute febrile diseases in humans, often resulting in lethality. The use of convalescent-phase human plasma is an effective treatment in humans infected with arenaviruses, particularly species found in South America. Despite this, little work has focused on developing potent and defined immunotherapeutics against arenaviruses. In the present study, we produced arenavirus neutralizing antibodies by DNA vaccination of rabbits with plasmids encoding the full-length gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 58 publications
1
49
0
2
Order By: Relevance
“…In contrast to mAbs, polyclonal antibodies that were reported to neutralize JUNV, MACV, GTOV, and SBAV were achieved by vaccination of rabbits with mixed plasmids encoding GPCs of the four NW arenaviruses (Golden et al, 2016). In our study, both antisera and JUNV GP1-specific IgG purified from antisera had some cross-neutralizing effect on the five NW clade B arenaviruses, although the results were only validated with VSV pseudotypes bearing arenaviral GPs, which may be different from those validated with actual viruses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to mAbs, polyclonal antibodies that were reported to neutralize JUNV, MACV, GTOV, and SBAV were achieved by vaccination of rabbits with mixed plasmids encoding GPCs of the four NW arenaviruses (Golden et al, 2016). In our study, both antisera and JUNV GP1-specific IgG purified from antisera had some cross-neutralizing effect on the five NW clade B arenaviruses, although the results were only validated with VSV pseudotypes bearing arenaviral GPs, which may be different from those validated with actual viruses.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to mAbs, polyclonal antibodies also play a role in combating JUNV infection. Polyclonal antibodies purified from DNA-immunized rabbits have been demonstrated to protect guinea pigs from a lethal JUNV challenge (Golden et al, 2016). In fact, horse antiserumderived polyclonal antibodies that demonstrated good efficacy against infectious diseases caused by highly pathogenic agents, such as Ebola virus (Wang et al, 2018a;Zheng et al, 2016), West Nile virus (Cui et al, 2016), H5N1 influenza virus (Lu et al, 2006), severe acute respiratory syndrome virus (Lu et al, 2005), and Middle East respiratory syndrome coronavirus (Zhao et al, 2017), have been extensively reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, his hypothesis needs to be confirmed. Recently, Golden et al 19 described a DNA vaccine that could be used as a pan-arenavirus immunotherapeutic.…”
Section: Basic Aspects Of the Sabiá Virusmentioning
confidence: 99%
“…An example of promising antibody therapy is a glycoprotein-specific IgG cocktail, produced by DNA vaccination, that has been demonstrated to protect experimental animals against lethal JUNV and GTOV challenge. Encouragingly, some, albeit limited, cross-neutralization was observed between the JUNV and MACV glycoprotein-specific sera [46]. …”
Section: Arenaviral Glycoproteins Are Targeted By Neutralizing Antibomentioning
confidence: 99%
“…The successful development of a JUNV vaccine has stimulated considerable interest in the development of vaccines to other arenaviruses and potentially cross-protective vaccines [46,4851]. …”
Section: Prospects For Arenaviral Vaccinesmentioning
confidence: 99%